(untitled) (Revista Contexto & Saúde, 2022)
ABSTRACT Introduction: The monitoring and continuous evaluation of the actions developed in Pharmaceutical Care are strategies for the search for quality, especially in hospitals. A good evaluation aims to reduce uncertainties, improve the effectiveness of actions and provide relevant decision-making by assisting in the service management policy. Objective: To develop an evaluation and monitoring matrix for the pharmacy of a hospital institution. Method: It is an evaluative study. In order to elaborate and validate the content the following steps have been developed: bibliographic review, proposition on dimensions and elaboration of indicators, focus group with experts to validate and prioritize the dimensions and application of the delphi technique to the indicators for relevance and valuation. Cronbach’s alpha coefficient has been used to measure the reliability of the indicators. Results: Five dimensions and 70 indicators have been identified for the evaluation of Hospital Pharmacy, distributed as follows: Care Management (n=15), Human Resources Management (n=13), Drug Management (n=13), Financial Management (n=12) and Patient Clinic Management (n=17). The dimension Drug Management has been prioritized by the specialists, finalized with nine indicators. Conclusion: The study has shown the importance of evaluation for Hospital Pharmacy management and the capacity of executing consensus methods to quality indicators in high complexity services. The instruments with indicators developed for the dimension Drug Management has shown evidence of validity and good reliability.